2019
DOI: 10.3390/ijerph16040670
|View full text |Cite
|
Sign up to set email alerts
|

Contamination, Sources, and Health Risks Associated with Soil PAHs in Rebuilt Land from a Coking Plant, Beijing, China

Abstract: This study investigated the polycyclic aromatic hydrocarbon (PAH) pollution in the reconstructed land of an abandoned industrial site: a coking plant in Beijing. To meet the needs of urban development, many factories have had to be relocated from city centers, and abandoned industrial sites often need to be transformed into residential land or urban green space through a series of restoration measures. It is necessary to study the level of residual pollutants and potential risks associated with industrial reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 36 publications
2
34
3
Order By: Relevance
“…The observed ILCR for humans due to PAHs during this study were comparable with ILCR reported for various Indian locations like Dhanbad (adults, 6.93 × 10 −5 , children,6.22 × 10 −5 ; adults, 1.82 × 10 −5 , children, 1.85 × 10 −5 ; adults, 3.36 × 10 −6 -7.53 × 10 −6 , children 2.65 × 10 −6 -8.19 × 10 −6 ) [ [14][15][16], Ghaziabad (adults 7.7 × 10 −5 , children 4.5 × 10 −5 ) [18], Gwalior (adults, 6.4 × 10 −5 , children, 2.4 × 10 −4 ) [19], Korba (adults, 6.7 × 10 −5 , children, 3.5 × 10 −5 ) [58] and Kurukshetra (adults, 8.1 × 10 −6 , children, 4.2 × 10 −5 ) [59]. ILCR was also comparable with reported for cities of other countries including Beijing, China (adults, 2.48 × 10 −6 -3.08 × 10 −6 , children, 1.56 × 10 −6 -2.69 × 10 −6 ) [35], and USA (6 × 10 −5 ) [60]. But was less than Mashad, Iran (adults, 6.2 × 10 −4 , children, 7 × 10 −4 ) [8], Kutahya, Turkey (adults, 5.71 × 10 −6 to 3.19 × 10 −4 ) [12], Guatemala (adults, 1.61 × 10 −4 ) [13], and higher than Yinma (children, 1.00 × 10 −6 to 1.18 × 10 −6 , adults, 1.10 × 10 −6 to 4.22 × 10 −6 ) [6], Liaohe (children, 4.03 × 10 −8 , adults, 1.14 × 10 −7 ) [7], Wuhan (adults 1.13 × 10 −8 to 3.54 × 10 −8 , children 9.23 × 10 −7 to 9.51 × 10 −6 ) [9], Gwangju in South Korea (adults, 8.41 × 10 −6 , children, 3.61 × 10 −7 ) [10], and North-West China (adults, 1.19 × 10 −9 Children, 1.79 × 10 −9 ) [11].…”
Section: Pearson's Coefficient Of Correlationsupporting
confidence: 77%
See 1 more Smart Citation
“…The observed ILCR for humans due to PAHs during this study were comparable with ILCR reported for various Indian locations like Dhanbad (adults, 6.93 × 10 −5 , children,6.22 × 10 −5 ; adults, 1.82 × 10 −5 , children, 1.85 × 10 −5 ; adults, 3.36 × 10 −6 -7.53 × 10 −6 , children 2.65 × 10 −6 -8.19 × 10 −6 ) [ [14][15][16], Ghaziabad (adults 7.7 × 10 −5 , children 4.5 × 10 −5 ) [18], Gwalior (adults, 6.4 × 10 −5 , children, 2.4 × 10 −4 ) [19], Korba (adults, 6.7 × 10 −5 , children, 3.5 × 10 −5 ) [58] and Kurukshetra (adults, 8.1 × 10 −6 , children, 4.2 × 10 −5 ) [59]. ILCR was also comparable with reported for cities of other countries including Beijing, China (adults, 2.48 × 10 −6 -3.08 × 10 −6 , children, 1.56 × 10 −6 -2.69 × 10 −6 ) [35], and USA (6 × 10 −5 ) [60]. But was less than Mashad, Iran (adults, 6.2 × 10 −4 , children, 7 × 10 −4 ) [8], Kutahya, Turkey (adults, 5.71 × 10 −6 to 3.19 × 10 −4 ) [12], Guatemala (adults, 1.61 × 10 −4 ) [13], and higher than Yinma (children, 1.00 × 10 −6 to 1.18 × 10 −6 , adults, 1.10 × 10 −6 to 4.22 × 10 −6 ) [6], Liaohe (children, 4.03 × 10 −8 , adults, 1.14 × 10 −7 ) [7], Wuhan (adults 1.13 × 10 −8 to 3.54 × 10 −8 , children 9.23 × 10 −7 to 9.51 × 10 −6 ) [9], Gwangju in South Korea (adults, 8.41 × 10 −6 , children, 3.61 × 10 −7 ) [10], and North-West China (adults, 1.19 × 10 −9 Children, 1.79 × 10 −9 ) [11].…”
Section: Pearson's Coefficient Of Correlationsupporting
confidence: 77%
“…Recently, elevated concentrations of seven PAHs (∑ of NPT, FLE, PHE, ANT, FLT, PYR & BaP) (956-2714 μg kg −1 ) were reported in soils from power station area, interstate bus terminals and heavy traffic intersections in Delhi [34]. On comparison with similar studies from other countries, the observed concentrations were much less than concentrations reported for Beijing (736 ± 894 μg/kg) [35], Orlando (3227 ± 4676 μg/kg) and Thampa (4562 ± 10,031 μg/ kg) Florida in USA [36], Shengli (2160 μg/kg) [37], Xian (2053 μg/kg) [38], Shandong (3016 μg/kg) [39], Nanjing (980 μg/kg) [40], Ulsan (810 μg/kg) and Pohang (2384 μg/ kg) [41], Kathmandu (1172 μg/kg) [42], Cape Town (4080 ± 2640 μg/kg) [43], and San Mateo Ixtatán (1401 μg/ kg) [13]. But, PAHs concentrations in our study were above than those reported from Gwangju (51.2 μg/kg) [10] and Gyeonggi (253 μg/kg) [41].…”
Section: Levels Of Pahsmentioning
confidence: 72%
“…SA corresponds to the surface area of dermal exposure (cm 2 day −1 ), the dermal adherence factor is referred to AF (mg cm −2 ), AT denotes the average life span (day), ABS is the dermal adsorption factor, and PEF corresponds to the particle emission factor (m 3 kg −1 ). People were divided in terms of age and gender in six groups, such as: [19]. The corresponding parameter values are given in Supplementary Table S4.…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…The most important and valuable aspect of this study is that soil samples have been taken from different layers, up to 4 m in depth, while in other studies, the greatest sampling depths were up to 20 cm [28], 40 cm [6], 50 cm [3] and 100 cm [22].…”
Section: Introductionmentioning
confidence: 99%